Eksplorasi keterkaitan Semangat Entrepreneurial dan Indeks Daya Saing Global - Gandhi Pawitan (Business Administration Department - Universitas Katolik Parahyangan, 2013)
Indonesia is facing a fundamental shift in demography and geography. The birthrates is declining, with improvement in the health facilities, as well as increasingthe proportion of individuals of productive ages. The advantages occurred in the con-ditions of growing individuals in the age group 15-64 years, and declining birth rates(fertility). Can this advantages used to increase the competitiveness of Indonesia?This condition shows the power of productive age, and is known as the de-mographic dividend. In the demographic dividend period, Indonesia has an abun-dance of potential human resources in the productive age. On the other hand thatentrepreneurship is a vehicle to enhance the nation’s competitiveness. But an in-creasing in entrepreneurial activity at a certain level does not necessarily improvethe competitiveness, it should increase significantly and continually.Keywords: exploratory analisys, demographic divident, entrepreneurial attitude,global competitiveness index